Amino Acids The Forum for Amino Acid, Peptide and Protein Research - Closs, Ellen I.; Meffre, Patrick; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer.)
Amino Acids is an international, fully Open Access, peer-reviewed journal dedicated to publishing high-quality research related to the chemistry, biochemistry, physiology, pharmacology, and toxicology of amino acids and related compounds. The journal aims to cover a broad range of topics related to amino acids, including their biosynthesis, catabolism, metabolism, transport, signaling, and functions in the body. The journal welcomes original research articles, reviews, rapid communications, and mini-reviews on all aspects of amino acids and their derivatives. The main focus of the journal is to publish research studies that enhance our understanding of the biological and physiological roles of amino acids in the human body as well as plants and microbes. The scope includes, but is not limited to: Chemical and structural properties of amino acids and proteins Protein synthesis, folding, and degradation Protein-protein interactions Enzymology and metabolism of amino acids Peptide and protein engineering Neurotransmission and signaling by amino acids and related compounds Therapeutic applications of amino acids in neurology, immunology, cancer, metabolic disorders and cardiovascular diseases Biotechnological applications of amino acids in plants Applied microbiology Role and function of amino acids and peptides in nutrition, health, and disease Amino acids in drug discovery and development Applications of amino acids and peptides as biomaterials and biocatalysts The journal also aims to provide a platform for researchers to publish their findings on the therapeutic applications of amino acids and their derivatives in the treatment of various diseases, such as metabolic and neurological disorders, cancer, and cardiovascular diseases. In addition, the journal features articles on the nutritional and dietary aspects of amino acids, such as their dietary intake, supplementation, and metabolism, and how these factors influence human health and disease. Overall, Amino Acids is an essential forum for researchers, academics, and clinicians interested in the chemistry, biochemistry, physiology, pharmacology, and toxicology of amino acids and related compounds. Founding Editor Gert Lubec, University of Vienna, Vienna, Austria .
Keywords: Biochemistry; Analytical chemistry; Biochemical engineering; Life sciences; 9; Neurosciences; Chemical Biology; Analytical Chemistry; Bioprocess Engineering; Life Sciences; Protein Biochemistry; Neuroscience